Economic Growth and Financial Development: A Causality Analysis and the Impact of the Recent Financial Crises-Evidence from European Countries. - Ioannou, Phoenie (2013)
The underlying study investigates the causal relationship between financial development and economic growth across European Countries over the period 1980-2012. It is also examined the impact of the recent Financial Crises on the development of the financial sector which is measured based on a bank-based scheme and a market-based scheme. These issues are analyzed by employing static panel data models such as pooled OLS, fixed and random effects. Moreover, dynamic panel data analysis is introduced and specifically a GMM-system methodology is employed for solving probable issues such as endogeneity of some explanatory variables, heteroskedasticity and serial correlation. The empirical findings showed a positive link between financial development and economic growth when the market based scheme was taken into account. On the other hand, bank based scheme seems to have a negative effect in boosting growth rates. Overall, taken financial development as a whole the results are somewhat ambiguous for the impact of finance to growth. Performing a Granger causality test for selected European counties aiming to identify the direction of causality between finance and growth, it seems that in most of the times the Development of the Financial sector Granger-causes the development of the real economic activity.